Plastic Bronchitis Following Fontan Procedure: A Case Report - Eser Doğan; Derya Aydın; Zülal Ülger; Ertürk Levent (Galenos Yayinevi, 2019)
Fibrinous bronchitis, also known as plastic bronchitis or pseudomembranous bronchitis, usually manifests clinically with non-productive cough and dyspnea. Prior to the expectoration of plaque formations, patients have a history of viral or other respiratory disease. Plastic bronchitis is an extremely rare and fatal complication associated with Fontan procedure. The condition is characterized by the formation of inspissated bronchial casts which may cause life-threatening airway obstructions. Although the pathogenesis of this condition remains unclear, it is believed to involve elevated pulmonary venous pressure, increased central venous pressure, and endobronchial lymphatic leakage. A 9-year-old male patient with Down syndrome underwent Fontan procedure 29 months earlier due to complete endocardial cushion defect and single ventricular physiology. The patient presented to the emergency department due to sudden-onset respiratory distress and fever (38.5 °C). Bilateral diffuse sibilant rhonchi, secretory rales, and intercostal retractions were noted during pulmonary system examination. Posterior-anterior chest x-ray showed cardiomegaly (cardiothoracic ratio=0.6) and bilateral diffuse infiltration. While under treatment, the patient experienced sudden-onset cough with expectoration of rubbery sputum in the form of branching bronchi-shaped casts. Samples of the inspissated sputum were sent to the Pathology and Microbiology departments for examination. The pathology report indicated fibrinoid material composed of a small number of inflammatory cells and bacterial plaques. Normal bacterial flora was identified in microbiological culture. Clinical presentation can vary from mild clinical findings to life-threatening symptoms. As in our patient, the diagnosis is made clinically, based on expectoration of bronchial casts or their detection during bronchoscopy. As our patient responded well to medical treatment, we proceeded with clinical follow-up. Plastic bronchitis is a very rare entity, and carries a poorer prognosis when it develops after congenital heart disease, as in our case.